BUSINESS DEVELOPMENT STRATEGY FOR NON-FINANCIAL PERSPECTIVE BALANCE SCORECARD METHODS TO INCREASE THE PERFORMANCE OF MSMEs IN INDONESIA DURING THE COVID-19 PANDEMIC - Mardinata Rusli, Yohanes; Surjadi, Merna (Dinasti Publisher, 2021)
The COVID-19 pandemic has affected the performance of companies, especially MSMEs in Indonesia. The purpose of this study is to determine and analyze how much the company's business strategy has an influence on improving company performance, especially MSMEs. This research has its own peculiarities and is unique because at the time this research was conducted it was in a world situation that was experiencing a pandemic, including Indonesia. The research data was collected using quantitative techniques from primary data sources, which collected 173 questionnaires from 200 questionnaires distributed to several restaurants, canteens, and beverage outlets including small and medium businesses in the Jakarta, Bandung, and Surabaya areas. Based on the test results using multiple linear regression, it can be concluded that: (1) The customer perspective has a significant influence on the performance of MSMEs in Indonesia, (2) the Internal Business Process Perspective has no significant influence on the performance of MSMEs in Indonesia, and (3) The Learning and Growth Perspective has a significant influence on the performance of MSMEs in Indonesia.